Influence of varying branched-chain amino acid ratio in diets containing corn gluten meal, L-isoleucine, and L-valine on 0–21 d turkey poult performance, relative mTOR activation, and apparent ileal amino acid digestibility - E.B. Estanich; K.M. Bowen; L.E. Knarr; E.A. Lynch; S.L. Noll; A.R. Garcia Morales; J.S. Moritz (Journal of Applied Poultry Research)
SUMMARY: The branched-chain amino acids (BCAA) leucine, isoleucine, and valine are essential AA needed for energy production, protein synthesis, and anabolic signaling functions via the mammalian target of rapamycin (mTOR) pathway in turkeys. Imbalanced BCAA ratios can lead to antagonism and degradation of limiting BCAA, particularly in diets with excess leucine. Concentrated corn proteins contain high levels of leucine and can alter BCAA requirements; however, L-Ile and L-Val may be added to correct BCAA ratios. This study evaluated the effects of varying dietary BCAA ratio using corn gluten meal, L-Ile, and L-Val on performance, mTOR activation, and apparent ileal AA digestibility in commercial turkey hens from 0 to 21 d of age. A 38.4% corn and 49.8% soybean meal diet served as the Control. In uncorrected high leucine treatments, feed intake, bird weight, and live weight gain decreased (P < 0.05), and feed conversion ratio (FCR) increased relative to the Control at d 14 (P < 0.05). Performance equivalent to the Control was induced by adding both L-Ile and L-Val at d 14 (P > 0.05), and FCR decreased relative to the Control at d 21 (P < 0.05). Relative mTOR activation numerically increased with high leucine diets compared to the Control (P = 0.13). BCAA digestibility was maximized in high leucine diets with additional L-Ile and L-Val (P < 0.05). These results demonstrate that diets containing excess leucine from concentrated corn proteins can decrease poult hen performance, but concomitant additions of L-Ile and L-Val may restore performance. In production settings, nutritionists should assess the costs associated with BCAA supplementation at practical levels vs. corn and soybean meal-based diets.